JPATS 2021
DOI: 10.25259/jpats_25_2021
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of COVID-19 patients with hypoxemia in Lagos, Nigeria

Abstract: Objectives: The coronavirus disease 2019 (COVID-19) pandemic is the current public health concern. Hypoxemia has been identified as an independent risk factor for mortality in COVID-19 patients regardless of age or sex. This study therefore aimed to assess the profile of COVID-19 patients with hypoxemia in Lagos, Nigeria and identify their associated socio-demographic and clinical risk factors, predictors, and outcomes. Materials and Methods: This was a retrospective cohort study in which data were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Elimian et al reported among others that age > 51 years is an independent factor associated with mortality [8]. Similarly, Akinbolagbe et al, and Ibrahim et al, in Nigeria also reported increased mortality among the aged population [9,10]. Age has also been described as the most important variable in predicting COVID-19 mortality in an international study [22].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Elimian et al reported among others that age > 51 years is an independent factor associated with mortality [8]. Similarly, Akinbolagbe et al, and Ibrahim et al, in Nigeria also reported increased mortality among the aged population [9,10]. Age has also been described as the most important variable in predicting COVID-19 mortality in an international study [22].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, a nationwide study by Elimian and colleagues reported that age greater than 51years, farming occupation, cough, vomiting and difficulty in breathing are associated with mortality among COVID-19 patients in Nigeria [ 8 ]. Another study in Nigeria by Akinbolagbe et al, showed that, age greater than 60 years, difficulty in breathing, and fever were independent predictors of hypoxaemia and death [ 9 ]. Similarly, in another study, hypoxaemia, obesity, diabetes mellitus and longer duration of symptoms were identified as predictors of mortality [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was carried out in a dedicated 120-bedded national COVID-19 isolation ward of the Lagos University Teaching Hospital (LUTH). [ 13 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%